A Q-Continuum of Off-Shell Supermultiplets. (31st January 2016) - Hübsch, Tristan; Katona, Gregory A.
Abstract : Within each supermultiplet in the standard literature, supersymmetry relates its bosonic and fermionic component fields in a fixed way, particularly to the selected supermultiplet. Herein, we describe supermultiplets wherein a continuously variable "tuning parameter" modifies the supersymmetry transformations, effectively parametrizing a novel "Q -continuum" of distinct finite-dimensional off-shell supermultiplets, which may be probed already with bilinear Lagrangians that couple to each other and to external magnetic fields, two or more of these continuously many supermultiplets, each "tuned" differently. The dependence on the tuning parameters cannot be removed by any field redefinition, rendering this "Q - moduli space " observable.